Brusberg Berichte 24. - Albrecht, Herbert; Bode, Ursula; Brusberg, Dieter; Büchner, Joachim; González, Julio; Harten, Jürgen; Honisch, Dieter; Melhop, Milburn; Smuda, Manfred; Wagner, Herbert H.; Galerie Brusberg, Hannover (Hannover : Galerie Brusberg, 1978)
Antes, Horst ; Arp, Hans (Jean) ; Bellmer, Hans ; Botero, Fernando ; Cimiotti, Emil ; Delvaux, Paul ; Diederichs, Peter ; Ernst, Max ; González, Julio ; Laurens, Henri ; Magritte, René ; Marow, Ernst ; Oelze, Richard ; Szymanski, Rolf ; Taylor, Evelyn ; Tübke, Werner ; Uhlmann, Hans ; Waske, Felix
Duits
boek